Effect of superheated steam inactivation on naturally existent microorganisms and enzymes of highland barley. (29th March 2019) - Wang, Haoran; Wang, Lili; Tong, Litao; Li, Zaigui
Summary: Superheated steam (SS) processing displayed noticeable effects on both microbial inactivation, including total bacterial count, Bacillus spp. and molds, and enzyme inactivation. Moisture content affected decontamination efficiency and recommendable moisture was 20%. Moisture adjusting method of spraying just before SS treatment was better than tempering. Molds were totally decontaminated by SS processing at 200 °C for 90 s and 120 °C for 180 s respectively. At 200 °C for 180 s, 99.98% of bacteria and 95.21% of Bacillus spp. were inactivated by spraying, while 99.95% of bacteria and 92.59% of Bacillus spp. were inactivated by tempering. The enzyme activity in highland barley processed with SS was decreased as processing time and temperature increased. Lipase showed better thermal resistance than peroxidase. Tempering was better in enzyme inactivation. SS treatment was effective in inactivating microorganisms and enzymes of highland barley, and could bring significant economic benefits to the highland barley industry. Abstract : SS treatment was effective in inactivating microorganisms and enzymes of highland barley, consequently extending the shelf life and bringing significant economic benefits to the highland barley industry.